2016
DOI: 10.1590/1678-4499.446
|View full text |Cite
|
Sign up to set email alerts
|

Potential of calcium silicate to mitigate water deficiency in maize

Abstract: ABSTRACT:The aim of this study was to evaluate the potential of calcium silicate to mitigate the effects of water deficiency in maize plants yield. A completely randomized factorial design, consisting of five combinations of calcium silicate (0, 25, 50, 75, and 100%) and five different soil moisture levels (30, 70, 100, 130, and 160%), was adopted.The following parameters were evaluated: soil matric potential, xylem water potential, silicon concentration, leaf dry weight, and dry mass

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 23 publications
(18 reference statements)
1
7
0
Order By: Relevance
“…The lack of effect of the soil water tensions and potassium silicate doses, isolated or under interaction, was observed on most yield parameters. The interaction between these two factors should be important for maize plants as a result of giving resistance to water stress, as previously reported (Marques et al, 2016). The absence of significant effects of the Si dose factor (isolated) on the productive parameters of the sweet corn did not necessarily imply that it had no influence on the results.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…The lack of effect of the soil water tensions and potassium silicate doses, isolated or under interaction, was observed on most yield parameters. The interaction between these two factors should be important for maize plants as a result of giving resistance to water stress, as previously reported (Marques et al, 2016). The absence of significant effects of the Si dose factor (isolated) on the productive parameters of the sweet corn did not necessarily imply that it had no influence on the results.…”
Section: Discussionsupporting
confidence: 59%
“…Farmers often avoid using silicate fertilizers for fear of increasing production costs. Nevertheless, the use of fertilizers as an exogenous source of Si in sweet corn, via soil or foliage spraying, has great potential for stimulating level of resistance to water stress (Marques et al, 2016). The outcomes of the present study may encourage the use of silicate fertilization in corn plants under water stress.…”
Section: Introductionmentioning
confidence: 77%
“…The activated Ca sensors can also bind to cis-elements of major stress-responsive gene promoters or can interact with DNA binding proteins regulating these genes, resulting in their activation or suppression [66,67]. In this context, Marques et al [68] reported a positive effect on maize production with the application of calcium silicate under water stress. Fan [33] concluded that Ca application at 10 mM achieved the highest maize yield under both normal and drought conditions while Naeem et al [29,34] found an increase in maize yield with the foliar application of Ca (40 mg L −1 ).…”
Section: Agronomic Traitsmentioning
confidence: 99%
“…Evidence of this is the fact that plants have evolved influx, efflux and channel-type transporters to actively uptake Si ( Ma and Yamaji, 2006 , 2015 ; Trembath-Reichert et al, 2015 ; Vivancos et al, 2016 ) as well as that yield increases when plant-available Si is added to the growing medium ( Tavakkoli et al, 2011 ). The beneficial roles of Si to various plants have been the subject of extensive research and include alleviation of abiotic stresses such as drought ( Marques et al, 2016 ), metal toxicity, and micronutrient deficiency ( Hernandez-Apaolaza, 2014 ); and biotic stress from pathogens ( Winslow, 1992 ; Vivancos et al, 2015 ) and herbivores ( Reynolds et al, 2009 , 2016 ; Ye et al, 2013 ). To date, there is increasing evidence of Si priming plants for defense against herbivore attack ( Reynolds et al, 2009 ; Hartley and DeGabriel, 2016 ).…”
Section: Discussionmentioning
confidence: 99%